APOE genotype, brain imaging, and neuropsychological testing markers of Alzheimer's disease: Data from the Strong Heart Study: Epidemiology: Dementia and risk in underrepresented populations. (7th December 2020) - Suchy‐Dicey, Astrid M; Nelson, Lonnie A; Su, Yi; Howard, Barbara; Longstreth, WT; Buchwald, Dedra; Reiman, Eric M
Abstract: Background: Carrying an APOE ε4 allele increases risk for Alzheimer's disease and related dementias. However, risk effects and prevalence of risk alleles are not consistent across races/ethnicities. Prevalence of cognitive impairment or dementia and attributable risk from APOE ε4 genotype are unknown in American Indians (AI). This project evaluated associations of APOE genotype with cranial imaging and cognitive testing markers of vascular and Alzheimer's dementias in a large, prospective, population‐based cohort of AI. Method: The Strong Heart Study recruited 4, 549 AI aged 45‐75 from 13 tribal communities across 3 major geographic regions in 1989‐1991. In 2010‐2013, all eligible surviving participants, then aged 65‐95, underwent cognitive examination including 3MS, WAIS, COWA, and CVLT‐II long delay free recall and cranial magnetic resonance imaging (MRI). APOE was genotyped from blood using ABI PRISM Linkage Mapping and DNA sequencing. Result: Most participants carried either 3.3 (73%) or 4.3 genotypes (23%). Clinical risk factors for dementia were prevalent, including high body mass index (mean>30), hypertension (80%), diabetes (48%), high LDL (39‐44%), chronic kidney disease (27%), and prior stroke (8‐9%). APOE ε4 carriers did not differ from non‐carriers in clinical factors, with the exception of serum LDL (103.9 mg/dL vs 96.7 mg/dL, P =0.015). Findings from MRI were also similar between genotypes, including presence of infarcts or hemorrhages, brain volume, and grade (0‐9) for white matter hyperintensities, sulcal widening, and ventricle enlargement. APOE ε4 carriers had marginally more WMH volume than non‐carriers. Cognitive examination scores were also similar, including Modified Mini Mental Status Examination (3MSE), Weschler Adult Intelligence Scale coding test (WAIS), Controlled Oral Word Association test (COWA), California Verbal Learning Test long delay free recall (CVLT). Conclusion: Despite evidence for higher risk of Alzheimer's and related dementias from presence of APOE ε4 allele among individuals from other populations, our study found little evidence of such an effect in elderly AIs. These findings raise intriguing questions about the presence of as‐yet‐unknown protective factors. Limitations of this study include cross‐sectional analyses and possibility of selective survival before the MRI examination. Future research should directly examine whether longitudinal changes in cognition and brain structure are associated with APOE genotype.